2017
DOI: 10.1016/j.ijheh.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sanitation on infectious disease and nutritional status: A systematic review and meta-analysis

Abstract: This review confirms positive impacts of sanitation on aspects of health. Evidence gaps remain and point to the need for research that rigorously describes sanitation implementation and type of sanitation interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
198
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(214 citation statements)
references
References 61 publications
9
198
2
5
Order By: Relevance
“…Nutrition has a close relationship with susceptibility to infection. Malnutrition by itself increases the host's susceptibility to infectious diseases, and these infections, in turn, have negative repercussions on the metabolism of the host, worsening the host's nutritional state . BMI is widely used as an index of an individual's nutritional status .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrition has a close relationship with susceptibility to infection. Malnutrition by itself increases the host's susceptibility to infectious diseases, and these infections, in turn, have negative repercussions on the metabolism of the host, worsening the host's nutritional state . BMI is widely used as an index of an individual's nutritional status .…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition by itself increases the host's susceptibility to infectious diseases, and these infections, in turn, have negative repercussions on the metabolism of the host, worsening the host's nutritional state. 19 BMI is widely used as an index of an individual's nutritional status. 20 Several studies have revealed that underweight is associated with the risk of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Improved access to safe water and sanitation is necessary for long-term cholera control and reductions in overall diarrheal disease burden [36][37][38]. We examined the impact of vaccination deployment strategies that targeted districts with the lowest access to improved water and sanitation as measured by WHO/UNICEF Joint Monitoring Programme for Water Supply, Sanitation and Hygiene (JMP) indicators [27,39].…”
Section: Discussionmentioning
confidence: 99%
“…The nonpharmaceutical interventions are helpful in decreasing the probability of contracting and transmitting the infection. [3][4][5] The people follow the messages of the ill effects of disease expansion through TV and radio advertisements and adopt precautionary measures like vaccination, [6][7][8][9][10][11] sanitation, 12 isolation, 13 and quarantine. 14 Funk et al 15 have studied the impacts of public awareness and local behavioral response on the spread of an infectious disease.…”
Section: Introductionmentioning
confidence: 99%